Associated factors of oral frailty in older adults with long-term T2DM duration of more than 10 years - Jian Yu; Anna Ye; Yang Fei; Dandan Wang; Yu Zhang; Xianwen Li (BMC Geriatrics)
Abstract Objective To identify the factors that affect oral frailty in older adults with type 2 diabetes mellitus (T2DM) with long-term disease duration of more than 10 years. Methods This cross-sectional study was conducted at a National Metabolic Center in China from October 2023 to March 2024. Participants with T2DM (aged ≥ 60 years and a disease duration > 10 years) underwent comprehensive dental examinations to assess functional natural teeth (FNT) counts and oral restoration behaviors. Oral frailty and cognitive function were assessed using the Oral Frailty Index-8 (OFI-8) and the Clock Drawing Test (CDT), respectively. Demographic and clinical data were extracted from the hospital information system. Univariate analysis and hierarchical multiple linear regressions were performed to identify associated factors of oral frailty. Results Among 211 participants (mean age 71.22 ± 6.35 years, mean diabetes duration 20.95 ± 7.34 years), the mean OFI-8 score was 5.08 ± 2.29, with 74.4% scoring ≥ 4 (indicating oral frailty). The final regression model was statistically significant (F = 19.101, P < 0.001). In the regression model, a lower number of FNTs was significantly associated with higher oral frailty scores (β = -0.263, P < 0.001), whereas different oral restoration behaviors vary in the effect on oral frailty, fasting blood glucose (FBG) (β = 0.131, P = 0.014) and cognitive impairment (β = 0.255, P < 0.001) were positively associated with OFI-8 scores. Conclusions The study found that older adults with T2DM and a disease duration exceeding 10 years had a higher likelihood of exhibiting oral frailty. Individuals with fewer FNTs and those exhibiting cognitive impairment are the potential intervention targets to be concerned. Strict glycemic control and timely oral restoration are recommended to reduce oral frailty incidence in this population. Clinical trial number Not applicable.